The roles of ageing and physical activity in determining the anabolic response to amino acids in skeletal muscle - Stephanie Gagnon (2022)
Ageing is associated with a progressive loss of muscle mass termed sarcopenia, increasing morbidity and mortality. The mechanisms underpinning sarcopenia are unclear, but a blunted anabolic response of skeletal muscle to amino acids (AAs) after nutrient ingestion is undoubtedly a major contributing factor. However, this anabolic response is also sensitive to altered physical activity levels, which are lowered in older individuals. Thus, whether this ‘anabolic resistance’ to AAs is a consequence of ageing or inactivity is unknown. The use of primary human skeletal muscle cells has provided enhanced understanding of the interacting signalling pathways and molecular events occurring in human skeletal muscle cells, and several studies indicate that these in vitro models also allow for the retention of some metabolic characteristics of the donor muscle fibres from which they were derived. The purpose of this thesis was to couple both in vivo human metabolism studies with skeletal muscle cell culture to improve our understanding of the roles of ageing and physical activity in the regulation of skeletal muscle size and acute growth responses to AA availability at the whole body and cellular level.In chapter 3, an in vitro experimental assay was developed to detect changes in protein synthesis and mTORC1 activity in response to AA availability in human skeletal muscle cells.The use of the SUnSET assay was investigated, and it was determined that depriving human myotubes of AAs for 6 hours allowed for in vitro protein synthesis levels to decrease to basal levels prior to stimulation with leucine. A new protocol of the SUnSET assay was also trialled, including the use of a longer incubation time for determining protein synthesis levels. The assays established in this chapter were used to replicate the protocols utilised in vivo in chapter 4.Chapter 4 explored the roles of physical activity and ageing on differences in anabolic responses in skeletal muscle following AA feeding in active young men (18-25 yrs), untrained older men (65-80 yrs), and trained or habitually active older men (65-80 yrs). Using stable isotope tracers coupled with muscle biopsies, the findings elucidated that there is an effect of feeding on stimulation of the mTORC1 pathway and MPS, alongside lower quadriceps muscle size and strength in older individuals. Type 1 fibre percentage and size was lower only in inactive older individuals, suggesting physical activity may specifically preserve type 1 fibres.Type 2 fibre size was lower in both groups of older individuals, suggesting these fibres may be the first to atrophy during ageing, irrespective of physical activity levels. Thereafter, using skeletal muscle cells derived from the same participants investigated in this chapter, these experiments mirrored the in vivo experiments and explored the response to an AA mixture at the cellular level. Myotubes derived from older inactive individuals were significantly smaller in diameter compared to myotubes derived from young or older active individuals. However, myotubes from all groups were able to successfully fuse, and time course experiments showed an effect of AA stimulation on the mTORC1 pathway, displaying similar responses when compared to the in vivo data.Finally, the role of individual AAs on mTORC1 signalling was investigated in chapter 5. Ten different AAs were investigated at 3 different concentrations in primary myotubes derived from young individuals. The three most potent AAs were then explored in primary myotubes derived from older individuals. These experiments showed leucine, arginine, and methionine were the most potent for activating the mTORC1 pathway and also stimulated this pathway in myotubes derived from older individuals, with differences between young and old observed in response to methionine.In conclusion, the work presented in this thesis demonstrated older individuals retain the capacity for mTORC1 activation in response to AAs and provides initial experimental data of examination of anabolic responses in vivo coupled with those in cultured myotubes (derived from the same individuals), further exhibiting properties of retained muscle metabolism in vitro.